Achromatic Contrast Sensitivity for Vertical Sine Wave Gratings in Adolescents and Adults - Maria José Nunes Gadelha; Michael Jackson Oliveira de Andrade; Olívia Dayse Leite Ferreira; Rosália Carmen de Lima Freire; Natanael Antonio dos Santos (Psicologia, 2010)
The aim of this study was to characterize the contrast sensitivity function (CSF) of adolescents and young adults. Was measured FSC for linear sine‑wave grating stimuli with spatial frequencies of 0.25, 1.0, 2.0 and 8.0 cpd, using the forced‑choice psychophysic method with two alternatives temporal. The measurements were performed with binocular vision and the medium luminance of 42.6 cd/m2. All participants had normal acuity and were free of ocular pathology. The analysis showed significant differences between the two groups in the low medium and high frequencies. The adults were more sensitive than adolescents in low frequencies (0.25 cpd) and adolescents were more sensitive than adults in middle and high frequencies (2.0 and 8.0 cpd). These results suggest that the process of development and maturation of the visual perception of contrast interacts differently with the mechanisms that process spatial frequencies.